Neuroprotectives: Herbs vs Heterocyclics - Bhandari, Divya Dhawal; Kaur, Prabhjot; Chopra, Hitesh; Lata, Suman (Scripta Medica, 2025)
Neurodegenerative diseases are described as the ones associated with the loss of any specific nerve function which results in either cell death or abnormal functioning of associated organ such as memory loss, tremors, difficulty in speaking and walking, loss of senses and numbness. A number of heterocyclic nuclei containing compounds are available in the market to treat neurodegenerative disorders and associated symptoms due to their concerned therapeutic potential. Ongoing research on these heterocyclics have confirmed their tremendous potential towards the treatment of neurodegenerative diseases. Although a number of heterocyclic containing compounds are already there in the market against various neurodegenerative diseases, but till date no specific treatment is available against any of the neurodegenerative disease, thus opening new area of research. Herbs are emerging as new area of research due to their wide availability and with lesser or no side effects. These days researchers are gaining interest towards the development of newer neurodegenerative agents derived from plants. This review is focused towards the comparison of various available herbs, heterocyclics and the compounds under clinical trials, against neurodegenerative diseases primarily focusing on Parkinson disease and multiple sclerosis.